KINERJA KELELAHAN CAMPURAN BETON ASPAL LAPIS AUS MENGGUNAKAN MATERIAL HASIL DAUR ULANG DAN POLIMER STYRENE-BUTADIENE-STYRENE - Pradani, Novita; Sugeng Subagio, Bambang; Rahman, Harmein (Jurnal Transportasi, 2011)
Pavement recycling technology, as an alternative technology in road pavement construction and maintenance, is continuously developed. The aim of this study is to modify recycled material by adding a polymer that is able to improvethe physical properties and performance of asphalt and recyled mixture. Asphalt mixture used in this study was Aspahlat Concrete-Wearing Course (AC-WC) containing Reclaimed Asphalt Pavement (RAP), fresh materials, asphalt Pen 60/70, and SBS polymer. The proportion of RAP used was 20% and 30% of the total weight of the mixture. For each RAP variation, asphalt Pen 60/70 was mixed with 0%, 2.5%, and 5% of SBS polymer. Fatigue performance of mixture was, then, measured using 4-Point Bending Test Apparatus. The results show that RAP asphalt has lower penetration and higher viscosity values. Fatigue test shows that the increase in the proportion of RAP will improve the fatigue resistance of the mixture.Keyword: Reclaimed Asphalt Pavement, SBS Polymer, fatigue performance.